PERCEPTION OF JAMU USAGE AT ROWOBELANG VILLAGE, BATANG DISTRICT - Asri, Kurnia Ika Setya; Octasari, Paulina Maya (Jurnal Wiyata Penelitian Sains dan Kesehatan, 2024)
Background: The use of traditional medicine as herbs increased relatively neither in developing countries nor developed countries. Efficacy of herbs trusted hereditary. People use herbs as treatment therapy and maintain the health of the body. Some herbs mix medicinal chemical materials illegally. Abuse of it can affect public perception about used herbs in Rowobelang Village, Batang District. Method: This research is a descriptive observational study using a questionnaire instrument containing respondents' sociodemographic data and ten statements to measure public perception about using herbs. The public perception profile was measured in three aspects, there were efficacy aspect, accessibility aspect and safety aspect. Data was taken by using purposive sampling. Results: This research uses 320 respondents as the sample who belong to the inclusion criteria. Characteristics of respondents who filled out the questionnaire are 36-45 years old (35%), high school educated (43,8%), female (63,4%), and have a job (66,5%). The highest aspect that had a high percentage was the efficacy aspect, and the lowest was the safety aspect (28,46%).Conclusion: The result indicates the public perception of herbs used in Rowobelang Village is in the good perception category (72,5%).